2008
DOI: 10.1007/s12257-008-0142-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production conditions from food waste by dark fermentation with Clostridium beijerinckii KCTC 1785

Abstract: The optimum conditions for biological hydrogen production from food waste by `äçëíêáÇáìã=ÄÉáàÉêáåÅâáá KCTC 1875 were investigated. The optimum initial pH and fermentation temperature were 7.0 and 40°C, respectively. When the pH of fermentation was controlled to 5.5, a maximum amount of hydrogen could be obtained. Under these conditions, about 2,737 mL of hydrogen was produced from 50 g COD/L of food waste for 24 h, and the hydrogen content in the biogas was 38%. Hydrogen production rate and yield were about 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 38 publications
2
27
0
7
Order By: Relevance
“…Using a pH-control strategy to enhance biohydrogen production from SH hydrolysate It has been reported that low pH inhibits H 2 production because it affects hydrogenase activity and many aspects of microbial metabolism, including utilization of substrate, biogas content, and types of organic acids [15,18,33]. Low pH of fermentation media usually results in lower intracellular ATP levels and causes inhibition of bacterial growth and change in their metabolic pathways (acidogenesis to solventogenesis) resulting in low H 2 production [21,33].…”
Section: Effects Of Temperature and Substrate Concentration On Biohydmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a pH-control strategy to enhance biohydrogen production from SH hydrolysate It has been reported that low pH inhibits H 2 production because it affects hydrogenase activity and many aspects of microbial metabolism, including utilization of substrate, biogas content, and types of organic acids [15,18,33]. Low pH of fermentation media usually results in lower intracellular ATP levels and causes inhibition of bacterial growth and change in their metabolic pathways (acidogenesis to solventogenesis) resulting in low H 2 production [21,33].…”
Section: Effects Of Temperature and Substrate Concentration On Biohydmentioning
confidence: 99%
“…Biohydrogen production is a complex process and is greatly influenced by many factors, including microorganism seeding, pH, temperature, organic loading rate, metal ions, and oxidation-reduction potential. Optimization of these factors and controlling suitable environmental conditions could enhance dark fermentative H 2 production [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Since the physicochemical H 2 production processes are energy-intensive and hazardous to the environment, there have been urgent needs for biological H 2 production from renewable materials. Though thermo-chemical methods of producing H 2 are an easier approach, biological methods are safer and economically viable (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on H 2 production are carbohydrate-based (Bai et al, 2004;Ding et al, 2008;Lin and Lay, 2004;Roychaudhury et al, 1988;Zhang et al, 2003) since these materials can be improved by inhibition of the activity of H 2 -quenching pathways or by reduction of H 2 and CO 2 partial pressure (Nath and Das, 2004;Ewan and Allen, 2005;Kim et al, 2008;Nandi and Sengupta, 1998;Hallenbeck and Benemann, 2002;Bai et al, 2004;Ding et al, 2008;Lin and Lay, 2004;Roychaudhury et al, 1988;Zhang et al, 2003;Das and Veziroglu, 2001;Lamed et al, 1988;Oh et al, 2003;Park et al, 2005;Kim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…KIM et al (2008) et al, 2014), conforme descrito na Equação 8 (item 3.4.2). A formação do ácido butírico como principal subproduto da produção de H2 pela cepa isolada é, provavelmente, responsável pelo rendimento de H2 relativamente baixo, quando comparada com outros trabalhos da literatura, conforme discutido anteriormente.…”
Section: 4unclassified